Dari Jalanan ke Jeruji: Studi Kasus Mengenai Proses Sosial yang Mendorong Terjadinya Tawuran - Ciek Julyati Hisyam; Naailaah Anggya Putri; -, Aqila Hasna Yunia; Bielva Fitriana Nurhasanah; Seftyyani Tri Rahma; Artha Leena Citra Setyowati (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study aims to analyze the phenomenon of student brawls in Indonesia, focusing on the social factors influencing such behavior. The method used is a qualitative approach with a descriptive research type. The research was conducted over one month, from October to December 2024. The informant in this study consisted of one inmate involved in a brawl, selected through purposive sampling techniques. Data collection was conducted through in-depth interviews and document analysis. The data obtained were analyzed using thematic analysis. The results of the study indicate that student brawls are triggered by various factors, including social environment influences, peer pressure, and individual failures in building a positive identity. The case studied shows that group solidarity often obscures individual fear and morality, leading to aggressive actions that can result in physical injury, damage to public facilities, and even loss of life. Referring to Karl Marx's conflict theory, this study analyzes that social conflict arises from the unequal distribution of power in society. This study emphasizes the importance of supervision from various parties, such as families, schools, and communities, to prevent deviant behavior among adolescents.